Legal Protection for the Implementation of Immunization in Post-Immunization Adverse Incidents - Riyanto, Ade; Rezza, Muhammad; Noor, Alpat; Darmawan, Didit; Yulius, Andre (Metromedia, 2023)
Immunization has been proven to be effective in reducing morbidity, disability and death. The government requires the public to undergo immunization, and regulations regarding rights and obligations in administering immunization have been regulated in Minister of Health Regulation Number 42 of 2013. Even though this regulation already exists, challenges arise, especially when Post-Immunization Adverse Events (AEFI) occur, which can haunt Immunization Implementers in carry out his duties. This study intends to explore legal protection and policies for Immunization Implementers based on these regulations in Indonesia. This study method uses a qualitative approach with a focus on normative juridical analysis. The results of the study show that the legal instruments for implementing immunization are adequate, but a lack of understanding of the law often raises concerns about the risk of Adverse Events Post-Immunization.